Produksi Kue Brownies sebagai Upaya Meningkatkan Nilai Ekonomi Singkong di Krajan Blimbing Dolopo Madiun - Muzakki, Hawwin (LP2M INSURI Ponorogo, 2020)
Cassava, one of the staple foods of Indonesian people beside rice and sago, is promoted by the government as rice consumption replacements, together with corn, sago or potatoes. Cassava is indeed very easy to plant in all types of land, as in Krajan Hamlet, Blimbing Village, Dolopo District, Madiun Regency where almost every house has cassava plants on its garden. This fact encourages the engagement team to take the initiative to provide training of creative cassava processing. This activity aims to increase the economical value of cassava, which is one of the assets in the Krajan Hamlet, and is expected to be able to increase the family income, most of which are former migrant workers. Through the ABCD (Asset Based Community Development) method with some of its tools, found that the innovative and creative cassava process training in the form of